Letter to Rita Dobson from Lorraine Kingdon - Lorraine Kingdon:::::: (1976)
This letter, dated March 22, 1976, is from the Hueneme Business and Professional Women's Club in Port Hueneme, California. Addressed to Rita Dobson, Chairman of Political Promotion and Political Education for the California Federation of BPW Clubs, it formally endorses Jane Tolmach for the California State Assembly, 36th District. The endorsement is brief and direct, expressing the club's support for her candidacy. The letter is signed by Lorraine Kingdon, President of the Hueneme BPW. Copies were sent to additional individuals and to the Jane Tolmach for Assembly Committee.